2017
DOI: 10.1021/acs.inorgchem.6b02713
|View full text |Cite
|
Sign up to set email alerts
|

Rational Synthesis and Investigation of Porous Metal–Organic Framework Materials from a Preorganized Heterometallic Carboxylate Building Block

Abstract: The tetranuclear heterometallic complex [LiZn(piv)(py)] (1, where piv = pivalate and py = pyridine) has been successfully employed as a presynthesized node for the construction of four porous metal-organic frameworks (MOFs) [LiZn(R-bdc)(bpy)]·solv (2-R, R-bdc; R = H, Br, NH, NO) by reaction with 4,4'-bipyridine (bpy) and terephthalate anionic linkers. The [LiZn] node is retained in the products, representing a rare example of the rational step-by-step design of isoreticular MOFs based on complex heterometallic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Tetranuclear coordination complex [Li 2 Co 2 (piv) 6 (py) 2 ] (1) was synthesized by a reaction of lithium pivalate salt Li(piv), polymeric amorphous [Co(piv) 2 ] n and pyridine in equimolar ratio in a mixture of CH 3 CN and THF. This synthetic methodic is similar to that for previously reported [Li 2 M 2 (piv) 6 ] (M = Ni, Co, Zn) complexes [30][31][32]. The compound 1 crystallizes in triclinic space group P−1 (Fig.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Tetranuclear coordination complex [Li 2 Co 2 (piv) 6 (py) 2 ] (1) was synthesized by a reaction of lithium pivalate salt Li(piv), polymeric amorphous [Co(piv) 2 ] n and pyridine in equimolar ratio in a mixture of CH 3 CN and THF. This synthetic methodic is similar to that for previously reported [Li 2 M 2 (piv) 6 ] (M = Ni, Co, Zn) complexes [30][31][32]. The compound 1 crystallizes in triclinic space group P−1 (Fig.…”
Section: Resultssupporting
confidence: 79%
“…The six carboxylate anions are directed perpendicularly to the Co−Li axis of the node, while Co-N bonds are directed along this axis. In general complex is isostructural to previously reported [Li 2 Zn 2 (piv) 6 (py) 2 ] [32]. The only difference is that one µ 2bidentate oxygen atom in carboxylate group of pivalate anion connected to lithium cation.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…[7][8][9][10][11] It is important that in many cases, the polynuclear structure of the metal moiety is preserved both upon replacement of N-donor ligands and carboxylate anions, which significantly expands the options for the chemical design of new heterometallic derivatives and allows one to manipulate the physical characteristics of molecules and even the crystals that are formed from them. [12] Cadmium(II) carboxylates, along with 3d-metal carboxylates, are attractive as a basis for the chemical design of practically important compounds. It was already shown that cadmium(II) trimethylacetate in the presence of alkaline earth metal ions is capable of forming CdÀ M II (M II = Mg, Ca, Sr) heterometallic tricyclic complexes [Cd 2 M(piv) 6 (lut) 2 ] (lut = 2,4lutidine).…”
Section: Introductionmentioning
confidence: 99%
“…The MOFs possessing versatile structures and desired properties are mainly dependent on the appropriate organic linkers [9,10], and the external synthesis conditions such as pH values, molar ratio of reactants, reaction temperatures, solvent system, and counter anions play important roles in deciding the resulting architectures [11][12][13]. Up to now, the N-or O-donor organic ligands have been employed extensively to construct functional coordination polymers [14][15][16]. Particularly, the N-donor compounds such as imidazole, pyrazole, triazole, and tetrazole can exhibit flexible coordination modes and afford more predictable coordination modes, as a result, these types of ligands have been extensively employed to construct diverse complexes.…”
Section: Introductionmentioning
confidence: 99%